Specific teacher competences for professor of programs In psychology - Rojas Zapata, Andrés Felipe; Luna Hernández, José Alberto; Hernández Arteaga, Isabel (SATHIRI, 2021)
The present article of results is product of a research that had for aim to describe the specific teaching competencies in the teacher’s work of undergraduate programs in psychology. Methodology: it were use the qualitative paradigm, ethnographic research and a sample of 13 professors from two universities. Results: teachers relate specific teaching competences with transversal teaching competences and the professional competences of the psychologist. Discussion: four specific teaching competences are established, the development of mental health, the knowledge of the multiple branches of psychology, the adaptability to sociocultural contexts and the recognition of the human. Conclusions: it is a subject that has not been studied, the theoretical investigation, critical reflection and analysis of practical experiences are needed to generate new knowledge that strengthens the teaching exercise and integral formation processes according to the educational needs of the psychologist in the century XXI.